The Challenge of Islamic Education Teaching in Inclusive Schools in Samarinda City - Elnurianda, Fitra; Fauzan, Umar; Hamzah, Syeh Hawib (Borneo International Journal of Islamic Studies, 2019)
Education is an individual right of citizen, including children with special needs. They study with regular students in inclusive school, including in Islamic Education subject which has an important role. In the process of teaching implementation, they need a special treatment. Objective of the research are: firstly, to describe the implementation of Islamic education teaching. Secondly, to describe supporting factors and the third is to describe barriers in inclusive schools in Samarinda City. Finding of this research reveals: firstly, the implementation of Islamic education (PAI) teaching in inclusive schools in Samarinda City requires several adjustments in teaching planning, implementation process and learning evaluation. Referring to National Examination, the system vary based on requirement from Department of Education. Secondly, the supporting factors found in this study are the application of humanistic education. Thirdly, the barriers in this study are found in school management and education system.